2003
DOI: 10.1093/hmg/ddg256
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid increases the SMN2 protein level: a well-known drug as a potential therapy for spinal muscular atrophy

Abstract: Proximal spinal muscular atrophy (SMA) is a common neuromuscular disorder causing infant death in half of all patients. Homozygous absence of the survival motor neuron gene (SMN1) is the primary cause of SMA, while SMA severity is mainly determined by the number of SMN2 copies. One SMN2 copy produces only about 10% of full-length protein identical to SMN1, whereas the majority of SMN2 transcripts is aberrantly spliced due to a silent mutation within an exonic splicing enhancer in exon 7. However, correct splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
251
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(267 citation statements)
references
References 38 publications
12
251
0
4
Order By: Relevance
“…The FL/D7 ratio in the SMA cells under study was similar, even though our patients had diverse genotypes and phenotypes. Previous reports have also shown a lack of correlation of FL/D7 ratios in blood cells, 20,28,32 fibroblasts 16 and lymphoblasts. 18 In the four haploidentical sisters, we found no differences in the FL/D7 ratios, either in fibroblasts or in lymphoblasts.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The FL/D7 ratio in the SMA cells under study was similar, even though our patients had diverse genotypes and phenotypes. Previous reports have also shown a lack of correlation of FL/D7 ratios in blood cells, 20,28,32 fibroblasts 16 and lymphoblasts. 18 In the four haploidentical sisters, we found no differences in the FL/D7 ratios, either in fibroblasts or in lymphoblasts.…”
Section: Discussionmentioning
confidence: 76%
“…In vitro experiments with phenylbutyrate (PBA) and valproic acid (VPA) -two well-known HDACi -have shown an increase in SMN mRNA and protein levels in SMA fibroblasts. [15][16][17] Similar studies with hydroxyurea (HU) in EBV-immortalized SMA lymphoblasts 18 have shown an increase in the FL-SMN/D7-SMN (FL/D7 ratio). Pilot trials with these drugs have been performed in SMA patients and results were promising, [19][20][21] leading to the development of placebo-controlled clinical trials.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Some therapeutic approaches aim to increase the amount of SMN protein produced by SMN2 through promoter activation, reduction of exon 7 alternative splicing, or both. [13][14][15][16][17][18][19][20][21][22] Some of these approaches are being investigated in ongoing or planned clinical trials, and great efforts have been done to identify the most appropriate clinical outcome measures for patients affected from various severities. 23 In this view, it would be very useful to have reliable biomarkers of disease severity and response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…HDAC-inhs have been tested in vitro and in vivo: hydroxybutyric acid was the first compound shown to increase SMN2 levels in lymphoblastoid cell lines from SMA patients and to also increase the lifespan of a SMA mice [Chang et al, 2001]. Since then, valproic acid, phenylbutyrate, trycostatin A, and SAHA have also been shown to increase SMN levels in vitro and/or to improve the survival of SMA models in pre-clinical studies [Brichta et al, 2003;Sumner et al, 2003;Andreassi et al, 2004;Hahnen et al, 2006;Avila et al, 2007;Narvel et al, 2008;Riessland et al, 2010]. Valproic acid and phenylbutyrate have been tested in patients with SMA but with discordant outcomes.…”
mentioning
confidence: 99%